The role of obsessive beliefs in patients with major depressive disorder. (January 2014) - Bahceci, Bulent; Bagcioglu, Erman; Çelik, Fatmagül Helvacı; Polat, Selim; Koroglu, Ayşe; Kandemir, Gökhan; Hocaoglu, Cicek
Abstract Aim. The aim of this study is to evaluate the differences in obsessional beliefs between patients with major depressive disorder (MDD) and matched healthy controls using the obsessive-beliefs questionnaire (OBQ). Methods. The study sample included 74 outpatients with MDD and 74 healthy subjects. The two groups were matched for age, gender, and education level. The diagnoses were based on the Diagnostic and Statistical Manual of Mental Disorder (DSM-IV). The severity of depression was measured with the Hamilton Depression Rating Scale (HAM-D). All participants filled out the 44-item OBQ. Results. The total and subscale OBQ scores [Responsibility/Threat Estimation (RT), Perfectionism/Certainly (PC), and Importance/Control of Thoughts (ICT)], were significantly higher in patients with MDD than those of the control group. There was a positive correlation between HAM-D scores and the OBQ subscale scores (RT, PC, and ICT) in the patients. Conclusion. Obsessional beliefs appear to be related to MDD.